2015
DOI: 10.1016/j.str.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide is Inserted into the Outer Membrane through An Intramembrane Hole, A Lumen Gate, and the Lateral Opening of LptD

Abstract: SummaryLipopolysaccharide (LPS) is essential for the vitality of most Gram-negative bacteria and plays an important role in bacterial multidrug resistance. The LptD/E translocon inserts LPS into the outer leaflet, the mechanism of which is poorly understood. Here, we report mutagenesis, functional assays, and molecular dynamics simulations of the LptD/E complex, which suggest two distinct pathways for the insertion of LPS. The N-terminal domain of LptD comprises a hydrophobic slide that injects the acyl tails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 43 publications
2
85
0
Order By: Relevance
“…The 40 C-terminal residues of LptE are apparently disordered and have not been observed in any crystal structure to date. As observed previously (Gu et al, 2015), a lumenal gate postulated to allow core oligosaccharide and O-antigen access to the extracellular surface is formed by two lumenal loops: lumenal loop 1 connects strand β1 of the LptD barrel to its N-terminal domain, while lumenal loop 2 connects strand β26 to the LptD C-terminus. In our truncated structures, lumenal loop 1 is ordered but lumenal loop 2 has no visible electron density despite the presence of the LptD C-terminus in the barrel.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The 40 C-terminal residues of LptE are apparently disordered and have not been observed in any crystal structure to date. As observed previously (Gu et al, 2015), a lumenal gate postulated to allow core oligosaccharide and O-antigen access to the extracellular surface is formed by two lumenal loops: lumenal loop 1 connects strand β1 of the LptD barrel to its N-terminal domain, while lumenal loop 2 connects strand β26 to the LptD C-terminus. In our truncated structures, lumenal loop 1 is ordered but lumenal loop 2 has no visible electron density despite the presence of the LptD C-terminus in the barrel.…”
Section: Resultssupporting
confidence: 55%
“…The availability of the first high resolution structures of LptDE shed light on the LPS insertion mechanism, including identification of a putative lateral gate through which LPS can be inserted into the outer membrane (Dong et al, 2014; Qiao et al, 2014). Further mutagenic analysis using an LptD depletion system identified regions of the structure that are important for function (Gu et al, 2015) and recently, LPS was shown to crosslink to a number of sites within LptDE, outlining a pathway for LPS transport (Li et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The two mutations described herein, lptD4213and lptD208, are overlapping deletions in LptD, a ␤-barrel protein responsible for the final step of LPS transport and assembly in the OM (40,41,70,71). Based on recent crystal structures (97,98), both mutations lead to the deletion of the alphahelical loop L4 situated on the extracellular surface of the protein, as well as a portion of either ␤7 or ␤8, respectively. Deletion of this loop may impair LptD function by reducing a few hydrogen bond interactions with the LptE plug and increasing extracellular access to the lumen of the ␤-barrel.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, once LPS is delivered to the N-terminal domain of LptD, a conformational change in LptDE would occur, enabling the saccharide portion of the LPS molecules to enter the ␤-barrel and travel to the cell surface, passing through the lateral gate of LptD. On the contrary, it has been proposed that the lipid A domain of LPS would pass first inside the ␤-jellyroll structure of the LptD N-terminal domain and then through the hydrophobic intramembrane open between the N-terminal and the ␤-barrel domains of LptD (66,79,80) (Fig. 2D).…”
Section: Minireview: the Lipopolysaccharide Transport (Lpt) Machinerymentioning
confidence: 99%